Coronary microvascular dysfunction in heart failure patients - Toya, Takumi; Nagatomo, Yuji; Ikegami, Yukinori; Masaki, Nobuyuki; Adachi, Takeshi (Frontiers in Cardiovascular Medicine, 2023)
Coronary microcirculation has multiple layers of autoregulatory function to maintain resting flow and augment hyperemic flow in response to myocardial demands. Functional or structural alterations in the coronary microvascular function are frequently observed in patients with heart failure with preserved or reduced ejection fraction, which may lead to myocardial ischemic injury and resultant worsening of clinical outcomes. In this review, we describe our current understanding of coronary microvascular dysfunction in the pathogenesis of heart failure with preserved and reduced ejection fraction.